Conjugated Polymers: Recently Advanced Polymer Materials Containing Dithieno[3, 2‐b:2′, 3′‐d]phosphole Oxide for Efficient Charge Transfer in High‐Performance Solar Cells (Adv. Funct. Mater. 26/2015). (July 2015) - Park, Kwang Hun; Kim, Yu Jin; Lee, Gi Back; An, Tae Kyu; Park, Chan Eon; Kwon, Soon‐Ki; Kim, Yun‐Hi
<x xml:space="preserve">Abstract</x> On page 3991 C. E. Park, S.‐K. Kwon, Y.‐H. Kim, and co‐workers report recently advanced donor polymers with a novel acceptor unit, dithieno[3, 2‐b:2′, 3′‐d]phosphole oxide (DTP) for high‐performance solar cells. Surprisingly, the introduction of this DTP unit in the polymer chains shows superior charge transfer properties with highly polarizable characteristics, and a power conversion efficiency of 7.08% is achieved.